UJI T DAN RELEVANSINYA TERHADAPKATAPENGARUH DAN EFEKTIVITAS DALAM PENELITIAN KUANTITATIF PENDIDIKAN - Choirun Nisa, Lulu (Universitas Ahmad Dahlan, 2011)
One of topics in quantitative research which students in Islamic Education Faculty, Walisongo State Institute of Islamic Studie handle for their theses is about implementation of inovatif teaching learning methods and then compare it with convensional methods to see the result of the implementation. For this study, students often unsure about the title because there are two opinion on it. First, the title should be Effectivity of Inovatif Method...., or the stitle should be The Influence of Inovative Method..... And both of these titles use the same statsitics test, i.e. Independent sample t test. Statistically, this study shows that influence is more appropriate for the case because the word of inluence refers to t-test definition. Otherwise independent sample t test will allowed to the word effective if there is assumption that an inovatif method is effective only if only the means of inovatif methods achievement is higher than convensionals achievement. Different assumtion about effectivity will bring different statistical test.